Inovasi Produk Asuransi Syariah : Tinjauan Literatur terhadap Tren Pasar dan Preferensi Konsumen - Pristiwanto Bani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to conduct a narrative review of the Sharia insurance product innovation literature, focusing on market trends and consumer preferences. This study is intended to provide a comprehensive understanding of the current developments in the Sharia insurance industry and identify opportunities for future product innovation. This literature review uses a narrative literature review method, conducted using academic databases from leading books and articles such as Scopus, Google Scholar and Web of Science. Searches using the keywords “product innovation,” “sharia insurance or takaful,” “market trends,” and “consumer preferences” resulted in a selection of relevant articles, which were then analyzed and categorized based on the main themes of sharia insurance market trends, consumer preferences, and product innovation. The review period covers publications from 2015 to 2024 to capture the current dynamics in the industry. The review results show a significant increase in interest in sharia insurance, especially after the global financial crisis. Market trends show a steady growth in adopting Sharia insurance across countries, with increasing consumer preference for products under Islamic principles. Product innovation has evolved from traditional models such as Mudarabah and Wakalah to more sophisticated approaches, including hybrid and Waqf-based products. The study also reveals the need for more diverse products tailored to the specific needs of local markets. The review highlights the need for further research on innovative Takaful product development. Sharia Insurance companies need to focus on better understanding consumer preferences and developing products that comply with Shariah principles and offer competitive added value. In addition, there is a need to explore the integration of digital technologies in the development and distribution of Takaful products. The study provides a comprehensive view of the current landscape of product innovation in the Takaful industry, emphasising market trends and consumer preferences. The review not only fills the gap in the existing literature but also provides a foundation for future research in this emerging field.